European firms and climate change 2020/2021 - Kalantzis, Fotios (European Investment Bank, 2021)
The European Union's COVID-19 recovery plan could be the impetus businesses need to invest in climate measures and prepare for the transition to a net-zero carbon economy. Our newest climate report looks at how firms' view these twin challenges and their preparedness to meet them. Firms are more aware of the physical risks posed by climate change, but less aware of the risks caused by the transition to clean energy. Almost half of EU firms surveyed are investing in climate change measures, compared with roughly one-third of US firms. Uncertainty over regulation and taxation continues to hamper climate investments. To green its economy, Europe needs a comprehensive strategy that will provide businesses with the guidance they need to invest in climate preparedness and the energy transition.